The African Growth Miracle - Young, Alwyn (Journal of Political Economy, 2012)
Measures of real consumption based on the ownership of durable goods, the quality of housing, the health and mortality of children, the education of youths, and the allocation of female time in the household indicate that sub-Saharan living standards have, for the past two decades, been growing about 3.4–3.7 percent per year, that is, three and a half to four times the rate indicated in international data sets.